Choroidal Thickness and Structural Glaucoma Parameters in Glaucomatous, Preperimetric Glaucomatous, and Healthy Eyes using Swept-Source OCT. Issue 5 (September 2017) - Akil, Handan; Al-Sheikh, Mayss; Falavarjani, Khalil Ghasemi; Francis, Brian; Chopra, Vikas
Purpose: To evaluate choroidal thickness (CT) and its relationship with retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer thickness (GCIPLT) in glaucomatous, preperimetric glaucomatous, and healthy eyes using swept-source optical coherence tomography (SS-OCT). Methods: Fifty eyes with primary open-angle glaucoma, 20 eyes with preperimetric glaucoma, and 20 age-matched healthy eyes were enrolled. Three-dimensional wide-field (12 × 9 mm) images were obtained using a SS-OCT instrument. Peripapillary CT and RNFL thickness, as well as macular CT and GCIPLT, were recorded. The correlation of the CT with nerve fiber layer and GCIPLT measurements was assessed. The association between CT and potential confounding variables including age, sex, axial length, intraocular pressure, and central corneal thickness was also examined. Results: Mean peripapillary CTs were 111.7 ± 41.7, 127.7 ± 40.1, and 120.8 ± 35.4 μm in glaucomatous, preperimetric glaucomatous, and normal eyes, respectively. There was statistically significant but weak correlation for the mean RNFL and mean peripapillary CT in glaucomatous subjects (r = 0.341, p = 0.04). There was a significant correlation between RNFL thickness and peripapillary CT in 1, 2, 5, and 6 clock hours of glaucomatous eyes (r = 0.410, p = 0.005; r = 0.316, p = 0.03; r = 0.346, p = 0.02; r = 0.35, p = 0.04, respectively). Mean macular CT was 181.5 ± 70.5, 187.4 ± 65.5, and 185.4 ± 76.4 μm in glaucomatous, preperimetric glaucomatous, and healthy eyes, respectively (p = 0.7). There was no statistically significant correlation between the mean GCIPLT and mean macular CT in all subjects (p>0.05). Conclusions: Choroidal thinning and its correlation with other parameters in patients with glaucoma should be further investigated with the proprietary software of SS-OCT.